KINETIKA PENURUNAN KADAR VANILIN SELAMA PENYIMPANAN POLONG PANILI KERING PADA BERBAGAI KEMASAN PLASTIK - R Bhaskara Katri Anandito; Basito Basito; Hatmiyarni Tri Handayani (AGROINTEK, 2010)
Flavour compound in vanilin (vanilin compound) is constructed during the production process of fresh vanilin bean into dry vanilin bean. The decreasing of vanilin level during the storage causes the decrease of quallity of vanilin level. This research is aimed to determine the kinetics decreasing of vailin level of dry vanilin in many plastic packaging during the storage. In this research, polietilen plastic (0,03 mm width), polipropilen (0,03 mm width) and plastic sack are used as the packaging of dry vanilin. The kinetic decreasing of vanilin level during the storage is determine by using Arrhenius kinetic. The result of this research shows that the decreasing of vanilin level in dry vanilin beans which are packaged by using polipropilen plastics is larger than packaged by using polietilen plastics and plastic sacks. The equation of the decreasing vanilin level for vanilin beans, packaged with polipropilen Y = -4030X + 9,685, polietilen Y = -3971X + 9,577 and plastic sacks Y = -3846X + 9,263.